Assessing IL-35 and IL-36 concentrations in Hemodialysis Patients with and without HCV - Safa Zuhair AlRheem; Hassnin Muiz Mohammad Hassan; Maitham Jasim Mohammed; Hawraa A. AlGhazaly (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: IL-35 and IL-36 are cytokines involved in immune modulation and inflammatory processes. Despite their established roles in various inflammatory and immune-mediated conditions, their specific contributions to end-stage renal disease (ESRD) and hepatitis C virus (HCV) infection in hemodialysis patients are not well understood. Objective: This study aimed to investigate the serum levels of IL-35 and IL-36 in ESRD patients undergoing hemodialysis, with and without HCV infection. Methods: A cross-sectional study was conducted, including 92 ESRD patients (47 HCV-positive and 45 HCV-negative) and 45 healthy controls. Serum levels of IL-35 and IL-36 were measured using enzyme-linked immunosorbent assay (ELISA). Results:IL-35 levels were comparable between controls (5.23 ± 4.24 ng/dL) and HCV-negative hemodialysis patients (4.83 ± 4.54 ng/dL; p = 0.665). However, HCV-positive patients exhibited significantly higher IL-35 levels (11.48 ± 4.13 ng/dL) compared to both controls and HCV-negative patients (p < 0.001). IL-36 levels were significantly elevated in both HCV-negative and HCV-positive hemodialysis patients (54.1 ± 21.7 ng/dL and 68.6 ± 52.4 ng/dL, respectively) compared to controls (26.3 ± 33.5 ng/dL; p < 0.001). Conclusion:L-35 is significantly upregulated in HCV-positive hemodialysis patients, indicating its potential role in immune regulation in the context of HCV infection. Elevated IL-36 in all hemodialysis patients reflects its involvement in the systemic inflammatory state associated with renal failure. These findings provide quantitative insights into the roles of IL-35 and IL-36 in hemodialysis and HCV, underscoring their potential as biomarkers or therapeutic targets.